ADM formulation of the General Relativity - Villegas Silva, Fulgenc (2017)
The study of the ADM formalism for the General Relativity Theory through the foliation methods on the Cauchy surfacesis is realized. The mathematical development that leads to the Hamiltonian formulation of General Relativity is presented explicitly.